Investigating the Relationships Between Public Health Literacy and Public Trust in Physicians in China's Control of COVID-19: A Cross-Sectional Study - Dongjin Chen; Qian Zhou; Cornelius B. Pratt; Zhenhua Su; Zheng Gu (Frontiers Media S.A., 2021)
Objective: Public trust in physicians and public health literacy (HL) are important factors that ensure the effectiveness of health-care delivery, particularly that provided during the SARS-CoV-2 pandemic. This study investigates HL as a predictor of public trust in physicians in China's ongoing efforts to control COVID-19.Methods: Data were gathered in February 2020 during the peak of the disease in China. Based on Nutbeam's conceptualization of HL, we measure HL vis-à-vis COVID-19 by using a six-item scale that includes two items each for functional, interactive, and critical HL. Trust in physicians was measured by assessing physicians' capability to diagnose COVID-19. A rank-sum test and ordinal logit regression modeling were used to analyze the data.Results: Two key findings: (a) trust in physician handling of treatment for COVID-19 is reported by about 74% of respondents; and (b) five of the six HL measures are positive predictors of public trust in physician treatment of the disease, with functional HL1 having the highest level of such association (coefficient 0.285, odds ratio 1.33%, p < 0.01).Conclusions: Improving public HL is important for better public-physician relationships, as well as for nations' efforts to contain the pandemic, serving as a possible behavioral, non-clinical antidote to COVID-19. Being confronted with the unprecedented virus, humans need trust. Health education and risk communication can improve public compliance with physicians' requirements and build a solid foundation for collective responses.